A GIS Support System for Road Safety Analysis and Management - Mahmud, Ahmad Rodzi; Radin Sohadi, Radin Umar; Mansor, Shattri (Universiti Putra Malaysia Press, 1998)
In diagnosing the cause traffic accidents, traffic engineers, planners and decision makers often need as much information as possible before deciding the appropriate countermeasure. In road safety analysis apart from producing the most accurate prediction from statistical figures, the need to visualize information geographically i always essential. This paper describes the implementation of SMKJ2, the method used to provide multiple ways of visualising accident data based on certain set of criteria, and the plan to incorporate multiple experts and knowledge base in to the system. The project, presently confined to the area of Seremban City Council of Negeri Sembilan, has been carried out in collaboration with The Royal Malaysian Police and The Road Safety Council.